Essays on human capital, growth and innovation: Political economy perspective - SIMA, Di (Institutional Knowledge at Singapore Management University, 2019)
The dissertation explores the role of human capital, education, and political institutions in the process of economic and political development. The first chapter shows that economic development such as secondary school enrollment rates during the democratization period exerts long-lasting effects on growth, possibly by giving permanent birthmarks to newly minted democratic institutions. Specifically, democracies born in weak development tend to have weak institutions and slow growth, while in contrast, those with adequate development at the political transition time establish strong institutions and achieve faster growth. The second chapter explores the effect of curriculum control in schooling on national innovation and individual creativity. The evidence suggests that a more centralized curriculum control, as indicated by more centralized official curriculum design together with more frequent high-stakes achievement exams, tends to reduce individual creativity and weaken national innovation. The third chapter studies how state capacity affects the investment in human capital, economic growth and democratization. It shows that autocracy may not necessarily inhibit economic growth when a country is poor but the state capacity is strong, while democracy facilitates growth more when a country is rich. In particular, the relationship between state development and democratization follows an inverted U-shape.